KONSEP SIMBOL KEBUDAYAAN: SEJARAH MANUSIA BERAGAMA DAN BERBUDAYA - Ning Ratna Sinta Dewi (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
Humans as God's most perfect creatures create their own culture and preserve it from generation to generation. Culture is part of the journey of human life. Based on history, culture or culture is something that cannot be separated from human life. Culture is the result of human creativity. Culture exists because of humans and humans develop a variety of cultures according to their needs and desires. Culture develops according to the human environment. Apart from being social creatures, humans also interact with fellow humans according to their habits and habits which in the end become a culture that is always carried out. Culture is a product of human creation. In other words, culture exists because humans created it and humans can live in the midst of the culture they created. Culture will continue to live when humans become residents and culture has enormous uses for all aspects of human life. Culture, which is a universal phenomenon, where every human being in the world has a culture, even though the shape (symbol) and style, of the culture that is owned varies from various tribes, nations, and races. In the end, the culture that humans have shows their similarities in accordance with human nature and every culture has a place and society is a place for that culture.